How has the French context shaped the organization of the Airbus Group?. Issue 4 (7th October 2014) - Stokes, Peter; Davoine, Eric; Oiry, Ewan; Barmeyer, Christoph; Mayrhofer, Ulrike
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine whether characteristics of French organizations can be found in the Airbus Group, ancient European Aeronautic Defence and Space Company (EADS) Group, and how these characteristics have evolved over time in comparison to German ones. Design/methodology/approach – This article presents an in-depth case study by using a contextual approach, considering influential factors which are likely to influence the evolution of organizations. Findings – The analysis shows that the Airbus Group reflects characteristics of French organizations: the importance of strategy, the principle of honour, centralization of decision and power, the role of the state in the capital and its influence via professional networks of its elite coming from the Grandes Ecoles. These findings confirm a relative continuity of national peculiarities over time. The recent evolution of the company also highlights the German influence, notably in terms of shares and management positions. Research limitations/implications – The case study demonstrates that the Airbus Group has become a multinational company where contextual elements and organizational structures regulate intercultural relationships of interests, influence and power. Originality/value – Five contextual factors are proposed, which allow to understand and structure the peculiarities of French organizations, in comparison to German ones as well as power distribution within the Airbus Group.